2013
DOI: 10.1089/ten.tec.2012.0712
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Native Derived Coronary Artery Tissue-Flap Model

Abstract: Although tissue-engineering approaches have led to significant progress in the quest of finding a viable substitute for dysfunctional myocardium, the vascularization of such bioartificial constructs still remains a major challenge. Hence, there is a need for model systems that allow us to study and better understand cardiac and vascular biology to overcome current limitations. Therefore, in this study, in toto decellularized rat hearts with a patent vessel system were processed into standardized coronary arter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 19 publications
0
15
0
2
Order By: Relevance
“…On the basis of these promising results, which indicated the feasibility of bioengineering a human tissue with innate vascularization, Aubin et al. decellularized the native cardiac muscle of a rat to establish a coronary artery tissue flap; its re-endothelialization in vitro indicated that it had great potential for further application [11]. More recently, Jank et al created decellularized limb composite tissue matrix.…”
Section: Introductionmentioning
confidence: 99%
“…On the basis of these promising results, which indicated the feasibility of bioengineering a human tissue with innate vascularization, Aubin et al. decellularized the native cardiac muscle of a rat to establish a coronary artery tissue flap; its re-endothelialization in vitro indicated that it had great potential for further application [11]. More recently, Jank et al created decellularized limb composite tissue matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Ingeniously, through perfusion-based decellularization, the organ's native vascular system is preserved down to the capillary level (Aubin et al 2013b, Uygun et al 2010, laying the foundation for a functional vascularization of the so engineered organs. In vivo-like vascularization, together with the innate characteristics of the three-dimensional ECM scaffold and the repopulation with adequate target cells in specialized culture systems have enabled the successful generation of functional, complex bioartifi cial organs in vitro (Uygun et al 2010.…”
Section: Whole-organ Tissue Engineeringmentioning
confidence: 99%
“…Furthermore, the analysis of architectural integrity of the ECM has evolved as a crucial step towards comprehensive characterization of the whole heart scaffolds generated by decellularization. It has been shown that the integrity of the vascular bed is of major importance for its functionality in terms of diffusion capacity and risk of thrombus formation upon blood perfusion (Aubin et al 2013b ). Moreover, important characteristics are the biomechanical behavior and the biocompatibility after decellularization.…”
Section: Whole-heart Decellularizationmentioning
confidence: 99%
“…Im Jahr 2013 konnte die Wiederherstellung des Endothels im Koronarsystem dezellularisierter Rattenherzen demonstriert werden [25]. Im Fall der übrigen vorrangig interstitiell ansäs-sigen Zellpopulationen, allen voran der Kardiomyozyten, stellt die optimale Rebesiedelung eine erhebliche Schwierigkeit dar.…”
Section: Zellquelle Besiedelung Und Invitro-kultivierungsbedingungenunclassified
“…Der aus aktueller Sicht größte Vorteil der Dezellularisierung gegenüber alternativen Verfahren der Matrixherstellung besteht in der Gewinnung von 3D-ECM-Komponenten mit einem integrierten vaskulären Netzwerk [25].…”
Section: Introductionunclassified